Study on seepage and failure characteristics of soil at the bottom of thick loose layer in thin bedrock area - Yanxin LIU; Yuliang WU; Fang KANG; Shuyun ZHU (Meikuang Anquan)
In order to study the seepage deformation and failure characteristics of the bottom soil mass of the thick loose layer in the thin bedrock area, the relevant safe mining and hydro-geological conditions are systematically analyzed based on the shallow area of the fifth and sixth mining areas in the west of Baodian Coal Mine. A mechanical model of the arrayed arch of clay sand particles at the mining fracture is established. From the perspective of mining conditions and the actual mechanical environment of the bottom soil, the seepage failure analysis of the bottom soil is carried out, and the mechanical equilibrium condition of critical instability and the critical flow velocity equation of transitional arch failure are presented. On this basis, through a large number of laboratory model tests, the critical hydraulic slope corresponding to the seepage failure of the soil at the bottom of the overlying loose layer under 7 different particle compositions and different mining fracture conditions was obtained. The results of the water-sand surge test under mining and non-mining conditions were compared and analyzed. It is found that the sand surge under mining conditions can be divided into three stages: the stable sand surge stage, the sudden reduction of sand surge and the water inrush stage.